Territorial Self-Government: From Local Communities to Self-Governing Community - O. M. Roy (Управленческие науки, 2025)
Territorial self-government represents a historical stage in the development of human civilization, emerging as a tool for regulating social relations at the sub-state level within the boundaries of local communities. It operates in the interests of these communities and with their direct participation. This form of governance originated during the intensification of class struggles between feudal lords and the citizens of free cities, ultimately granting the latter special rights as municipal corporations. However, the concept of “territorial self-government” is not identical to “local self-government,” as it is not confined to city boundaries but serves as a mechanism for territorial distinction at various levels. The functional diversity of territorial self-government is explained by historical, economic, and political factors that shaped the administrative territorial systems of modern states. Today, it acts as a means of distributing powers between different levels of public authority in addressing pressing social issues. The study aims to identify the characteristics and criteria of self-governance in territories and their role in enabling local communities to attain the status of self-governing entities. Recognizing these characteristics will help establish stable boundaries for the activities of self-governing communities using the so-called Functional Self-Governance Limit (FSG). This concept is necessary for evaluating (within socially accepted and rational limits) the costs of using a centralized governance model versus resolving community issues primarily through internal resources. Using the method of typological groupings, the study classifies different types of local communities in Russia based on selected criteria. The article also presents key indicators for assessing the FSG of municipal formations and examines conditions that facilitate both the transformation of individual civic attitudes into collective interests and the acquisition of self-governing status by local communities. The findings contribute to the development of a modern concept of local self-government in Russia and inform adjustments to ongoing municipal reforms.